Pengaruh Bahan Organik, Pupuk P, dan Bakteri Pelarut Phosfat Terhadap Keragaan Tanaman Kelapa Sawit pada Ultisol - Dewi Riniarti; Any Kusumastuti; Bambang Utoyo (Politeknik Negeri Lampung., 2012)
This study was aims to determine the effect of organic matter kind, phosphate fertilizers, phosphate solubilizing bacteri, and an interaction effect between type of organic matter with phosphate fertilizers, and phosphate solubilizing bacteri on vigour of oil palm at ultisol. The study was designed as a factorial in a randomized block design and each treatment was repeated 3 (three) times. The treatment consisted of 3 (three) factors. First factor were kind of organic matter: bagase and empty fruit bunches of oil palm, and without organic matter; second factor were Phospate fertilizer consisted of 45 grams of P2O5 per tree (the recommended dose) or 125 g SP-36 and 56.25 g per tree (125% recommended dose) or 156.25gSP-36; and third factor were with and without of posphat solubilizing bacteri. The results showed that: the organic material bagasse provided vegetative characters (leaf number, petiole length, leaf angle, leaf chlorophyll content, and in the number of leaves) of oil palm plantations in the Ultisol was better than empty fruit bunches of oil palm plantations in ultisol, and empty fruit bunches of palm oil gave the generative character (the number of female flowers, sex ratio) on oil palm plantations in the Ultisol better than bagasse. Key words: organic matter, phosphate fertilizer, phosphate solubilizing bacteria,vigour of oil palm before producted, and ultisol.